In Concreto Antinomies, Predictability, and Lawmaking. (12th January 2021) - Feis, Guglielmo
Abstract: This paper investigates whether or not cases of in concreto antinomies (ICAs for short, also called indirect antinomies, accidental antinomies, normative conflicts due to the facts, predicaments, or paranomies) can be predicted. I distinguish two main theoretical positions: "Prodetection" argues that we can predict in concreto antinomies; "unpredictability" argues that we cannot predict them. I exemplify the two positions by relying on a disagreement found in the literature; then, after reviewing that disagreement, I (i) provide arguments for both positions; (ii) highlight the problematic issues for a definition of in concreto antinomy based on conceptual independence; (iii) point out some problems in Martínez Zorrilla's threefold conception of normative conflicts; and (iv) advocate the need to introduce a case for "practically unpredictable" normative conflicts.